INFLUENCE OF CHOLINE ALFOSCERATE ON VISUAL PERCEPTION IN PATIENTS WITH AMBLYOPIA - I.E. Aznauryan; I.S. Bagrova (Педиатрическая фармакология)
Amblyopia is a frequent disorder in pediatric ophthalmology. The term of amblyopia refers to reduced vision caused by limited visual sensory stimulation (visual deprivation) at a time of visual system development, so the vision can not be improved by proper sunglasses. Apparatus treatment of amblyopia have limited effect in rehabilitation of children with moderate (lens corrected visual acuity between 0.2 and 0.3) and severe (lens corrected visual acuity below 0.2) amblyopia. Novel data concerning the use therapeutic agents affecting neural impulse transmission in patients with amblyopia have emerged over the recent years. The union of centers for vision care in children and adolescents «serene vision» has investigated the influence of agents containing choline alfoscerate on vision of children with refraction amblyopia. We have observed that complex therapy including choline alfoscerate agents has significantly improved the lens corrected visual acuity and visually induced potentials and has provided better results lasting through all the period of follow up (1 year).Key words: refraction amblyopia, choline alfoscerate, children